Autoimmune polyglandular syndrome type 2 in the form of Carpenter syndrome in a 16.5-year-old girl - Hanna Nowak; Dominika Szwacka; Marek Niedziela; Witold Stankiewicz; Monika Obara-Moszyńska (Pediatria Polska, 2024)
Autoimmune polyglandular syndrome type 2 (APS-2) is the coexistence of Addison disease and at least one of the disorders like autoimmune thyroid diseases and/or type 1 diabetes mellitus. We discuss the case of 16.5-year-old girl who had been diagnosed with APS-2 at the early age of 13.5 years. The girl presented recurrent abdominal pain and emesis for about 3 years, occurring about every 6 months. Moreover, in physical examination, characteristic skin hyperpigmentation furrows in the hands, nipples, and mucosa in the oral cavity were noticed. Due to the clinical picture and laboratory data, autoimmune thyroiditis and primary adrenal insufficiency were diagnosed. After initiating substitution treatment, the girl developed full-blown diabetes mellitus, probably masked earlier after primary adrenal insufficiency. It should be kept in mind that during the diagnosis of autoimmune disease, other autoimmune disorders may coexist; thus, such patients should be under specialists’ close supervision.